Pengaruh Konseling Kelompok Dengan Teknik Self-Management Terhadap Prokrastinasi Akademik - Maureta, Fransiska Della; Khoirunisa, Afifah; Salsabila, Alifia Nur; Galluh Arindhani, Gusti Ayu; Dea Saraswati, Ida Ayu (CV. Publikasi Indonesia, 2022)
This experimental study was conducted to determine whether there is an effect of self-management on academic procrastination. This study uses a true experimental research design with the type of Solomon Four Group Design. Participants in this study were 60 university students in Surabaya who were given a pretest to determine whether these students had a high level of procrastination. The measuring instrument used in this study is the Tuckman Procrastonation Scale (TPS). The results of the pretest showed that 40 students had a high level of procrastination, then the 40 students were randomly assigned (random assignment) into two groups. There were 20 students in the control group and 20 students in the experimental group. In accordance with the type of research used, each group was divided into four groups and received different treatment. The first and third experimental groups will receive group counseling using self-management techniques and will be given a pretest and posttest, while the second and fourth experimental groups will only receive counseling using self-management and pretest techniques. The first and third control groups will receive a pretest and posttest, while the second and fourth control groups will not receive treatment and will only receive a posttest. The results of this study indicate that the null hypothesis of this study is accepted, that is, there is no influence between self-management techniques and academic procrastination.